Ética, transparência e responsabilidade social corporativa - Alledi Filho, Cid (2002)
This thesis defines, relates the topics, suggests an implantation model, and demonstrates the purpose and the importance of the social responsibility in the organizations. To illustrate, are mentioned along the text several examples of national and international organizations that already adopt the practices of the social responsibility. This work demonstrates the importance of ethics and transparency in the context of the social corporate responsibility.